Maximally permissive coordinated distributed supervisory control of nondeterministic discrete-event systems - Su, Rong. (2013)
In supervisor synthesis for discrete-event systems achieving nonblockingness is a major challenge for a large system. To overcome it we present an approach to synthesize a deterministic coordinated distributed supervisor under partial observation, where the plant is modeled by a collection of nondeterministic finite-state automata and the requirement is modeled by a collection of deterministic finite-state automata. Then we provide a sufficient condition to ensure the maximal permissiveness of a coordinated distributed supervisor generated by the proposed synthesis approach.